2018
DOI: 10.1103/physreva.97.022707
|View full text |Cite
|
Sign up to set email alerts
|

Theory of excitation of Rydberg polarons in an atomic quantum gas

Abstract: We present a quantum many-body description of the excitation spectrum of Rydberg polarons in a Bose gas. The many-body Hamiltonian is solved with a functional determinant approach, and we extend this technique to describe Rydberg polarons of finite mass. Mean-field and classical descriptions of the spectrum are derived as approximations of the many-body theory. The various approaches are applied to experimental observations of polarons created by excitation of Rydberg atoms in a strontium Bose-Einstein condens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 66 publications
2
59
1
Order By: Relevance
“…Studying the line shapes of the excitation spectra revealed sharp lines caused by the formation of molecules in the few-atom regime, which turn into a broad shift in the many-atom limit (Gaj et al, 2014), where a Rydberg polaron can be formed (Camargo et al, 2018). The theoretical description of Rydberg polarons has been provided by (Schmidt et al, , 2018b in terms of the functional determinant approach. The role of the atomic ion in such systems has so far been rather marginal.…”
Section: Schemes Involving Rydberg Excitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying the line shapes of the excitation spectra revealed sharp lines caused by the formation of molecules in the few-atom regime, which turn into a broad shift in the many-atom limit (Gaj et al, 2014), where a Rydberg polaron can be formed (Camargo et al, 2018). The theoretical description of Rydberg polarons has been provided by (Schmidt et al, , 2018b in terms of the functional determinant approach. The role of the atomic ion in such systems has so far been rather marginal.…”
Section: Schemes Involving Rydberg Excitationsmentioning
confidence: 99%
“…II.E). Polarons are attracting increasingly large interest in the ultracold quantum matter community (Ardila and Giorgini, 2016;Ashida et al, 2018;Camargo et al, 2018;Casteels et al, 2013;Guenther et al, 2018;Hu et al, 2016;Jørgensen et al, 2016;Levinsen et al, 2015;Parisi and Giorgini, 2017;Schmidt et al, 2016Schmidt et al, , 2018bShchadilova et al, 2016) as the simplest example of nontrivial quantum field theory. In this arena, ion-atom systems could provide new insight into the problem, especially in the strong coupling regime (Casteels et al, 2011;Grusdt et al, 2017;Schurer et al, 2017;Tempere et al, 2009), as well as allow to study the effects of long-range interactions.…”
Section: B Quantum Simulationmentioning
confidence: 99%
“…The reverse RF scheme had been implemented for the observation of the full impurity spectral function by Kohstall et al [67], and found multiple applications in the observation of polaronic physics with ultracold atoms [31,58,67,70,[92][93][94][95].…”
Section: A Radio-frequency Spectroscopymentioning
confidence: 99%
“…These are characterized in terms of Feynman diagrams by a vertex joining two impurity lines and two phonon lines. Such processes have also been shown to be crucial for the description of Rydberg polarons [30]. This realization has lead to intense theoretical efforts to explicitly incorporate the extended Fröhlich interactions in various analytical methods that were developed for and applied to the Fröhlich model [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%